2021
DOI: 10.1186/s12890-021-01549-9
|View full text |Cite|
|
Sign up to set email alerts
|

GPC3 affects the prognosis of lung adenocarcinoma and lung squamous cell carcinoma

Abstract: Background Glypican 3 (GPC3) is a heparin sulphate proteoglycan whose expression is associated with several malignancies. However, its expression in non-small-cell lung carcinoma (NSCLC) is limited and ambiguous. This study aimed to comprehensively evaluate the expression of GPC3 in NSCLC and develop a risk-score model for predicting the prognosis of NSCLC. Methods The gene expression profiles of lung adenocarcinoma (LUAD) and lung squamous cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“… Kim et al (2003) demonstrated GPC3 to be a candidate gene for lung tumor suppression. Ning et al (2021) found GPC3 expression was significantly correlated with gender and tumour stage in LUAD samples. IL7R has been explored as aggressive tumor features for patients with LUAD: KRAS mutation, larger tumor size, lymphovascular invasion, high-grade morphology, and more frequent recurrence ( Suzuki et al, 2013 ).…”
Section: Discussionmentioning
confidence: 79%
“… Kim et al (2003) demonstrated GPC3 to be a candidate gene for lung tumor suppression. Ning et al (2021) found GPC3 expression was significantly correlated with gender and tumour stage in LUAD samples. IL7R has been explored as aggressive tumor features for patients with LUAD: KRAS mutation, larger tumor size, lymphovascular invasion, high-grade morphology, and more frequent recurrence ( Suzuki et al, 2013 ).…”
Section: Discussionmentioning
confidence: 79%
“…GPC3 is highly expressed during the fetal period, and its expression level is reduced after birth. GPC3 is overexpressed in hepatocellular carcinoma (HCC), embryonal tumors, melanoma, and some germ cell tumors, and is closely related to tumorigenesis and prognosis ( 32 , 33 ). These key genes play an important role in a variety of diseases, but their function in HIRI is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that GPC 3 may be a lung tumour suppressor gene that is downregulated by tobacco exposure [97,98]. However, GPC 3 expression has been described in several lung squamous cell carcinomas (LSCC) [21,26,27]. A study by Kim et al investigated GPC 3 expression and its role in lung cancer [97].…”
Section: Gpc 3 In Lung Cancermentioning
confidence: 99%
“…GPC 3 expression is also upregulated in most embryonic tissue, such as placenta and liver, but downregulated in the adult tissue of corresponding organ (Figure 3) [11]. In these tissues, GPC 3 expression is predominantly observed during development, with expression peaking in-utero before downregulation after birth [16,21,27]. Hence, this suggests the important role of GPC 3 in developmental morphogenesis [28].…”
Section: Introductionmentioning
confidence: 99%